2022
DOI: 10.1093/stcltm/szac005
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell Therapy for Neuroprotection in the Growth-Restricted Newborn

Abstract: Fetal growth restriction (FGR) occurs when a fetus is unable to grow normally due to inadequate nutrient and oxygen supply from the placenta. Children born with FGR are at high risk of lifelong adverse neurodevelopmental outcomes, such as cerebral palsy, behavioral issues, and learning and attention difficulties. Unfortunately, there is no treatment to protect the FGR newborn from these adverse neurological outcomes. Chronic inflammation and vascular disruption are prevalent in the brains of FGR neonates and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 143 publications
0
3
0
Order By: Relevance
“…The title of this manuscript seems to require an unambiguous answer to the question: do vesicles formed by mesenchymal stromal stem cells contain functional mitochondria? This question arose from the general ideas that, firstly, the introduction of MSC into the affected biological system has a therapeutic effect [30][31][32][33][34] and, secondly, a therapeutic effect similar in direction can be obtained from the introduction of the medium in which MSC are cultivated, or its concentrate, and even better with the use of products obtained by centrifugation of the culture medium in which vesicular particles were detected [35,36].…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
“…The title of this manuscript seems to require an unambiguous answer to the question: do vesicles formed by mesenchymal stromal stem cells contain functional mitochondria? This question arose from the general ideas that, firstly, the introduction of MSC into the affected biological system has a therapeutic effect [30][31][32][33][34] and, secondly, a therapeutic effect similar in direction can be obtained from the introduction of the medium in which MSC are cultivated, or its concentrate, and even better with the use of products obtained by centrifugation of the culture medium in which vesicular particles were detected [35,36].…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
“…Finally, a regenerative medicine approach could also prove effective to rescue the loss of brain cell populations. Several preclinical and clinical studies have reported that administration of stem cells or their derivatives have regenerative and neuroprotective effects in fetuses with fetal growth restriction 63,64 . To date, this approach has not been tested in CDH fetuses, likely due to the lack of understanding of the pathophysiology of brain injury, which is now unveiled by the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a regenerative medicine approach could also prove effective to rescue the loss of brain cell populations. Several preclinical and clinical studies have reported that administration of stem cells or their derivatives have regenerative and neuroprotective effects in fetuses with fetal growth restriction (60, 61). To date, this approach has not been tested in CDH fetuses, likely due to the lack of understanding of the pathophysiology of brain injury, which is now unveiled by the current study.…”
Section: Discussionmentioning
confidence: 99%